Suspended Sediment Yield Analysis Using a Continuous Monitoring System in the Sg. Pangsun Watershed, Ulu Langat, Selangor - Gerusu, Geoffery James (1999)
The need for reliable sediment yield data is a topic which generates much discussion especially among hydrologists, scientists and those concerned with the river system. Various methods were used in the past, the most popular being the use of sampled sediment data to equate with river discharge to obtain sediment load. While river discharge can be accurately computed, sediment discharge presents greater difficulty. This study assesses the use of total suspended sol ids (TSS) analyser in generating suspended sediment data from the Sg. Pangsun watershed, a small headwater catchment located in Ulu Langat, Selangor. The steep montane basin, about 2.6 km² lies on the southern flank of the Main Range. The study catchment was equipped with rainfall and water level recorders to assess the hydrological characteristics of the area. The TSS analyser uses a sensor which transmits information to an analyser. The TSS readings were stored electronically in a data logger and downloaded once a fortnight using a notebook. The annual suspended sediment loads of Sg. Pangsun catchment was 21.1 tonnes or 8.1 t/km²/yr. The suspended sediment loads retrieved were regarded as actual values, and then were compared against data deriving from conventional methods such as uncorrected and bias-corrected rating curves. The rating-curve data have been grouped according to all-stage and stage-differentiated to provide various rating relationships. The use of uncorrected rating curves based on all-stage and stage-differentiated data overestimated actual annual sediment loads by +32.7% and +26.1 % respectively. Bias-corrected rating curves based on all-stage and stage-differentiated data, however, gave far higher overestimated loads by more than + 100% compared to actua1loads. In this study, the use of different time-based such as hourly, daily and monthly discharge data underestimated the actual annual suspended sediment loads computed using 15-minute time-based by -2.8%, -20.4% and -39.8% respectively. The results suggested the TSS analyser would be of tremendous use for studies demanding accurate suspended sediment concentration monitoring.